China’s strategies and policies towards the three Indochinese countries in the period 1949-1954 - Mai, Nguyen Thi (Edelweiss Applied Science and Technology, 2025)
On October 1, 1949, the People’s Republic of China declared its establishment in the context of the Cold War, with a hot war taking place on China’s border—the Indochina War. In that complex context, Indochina was China’s traditional sphere of influence and security shield. Therefore, the problem for China was how to protect the newly established young state while creating a peaceful and stable environment both domestically and internationally for economic development. Moreover, China also wanted to establish diplomatic relations with Western countries to utilize capital, science, and technology to develop the economy and modernize the country. China needed a solution to the Indochina problem to achieve the aforementioned goals. The article will analyze the interests of significant countries towards the Indochina region since World War II, examine the situation in China to understand what China’s goals were during this period, and the measures China took towards the three Indochina countries to clarify the picture of China’s policy towards these countries from 1949 to 1954.